2018
DOI: 10.5173/ceju.2017.1517
|View full text |Cite
|
Sign up to set email alerts
|

Is magnetic resonance imaging helpful in detecting significant prostate cancer in patients with haematospermia, normal PSA and DRE. A single institution, observational, and retrospective study in a United Kingdom hospital

Abstract: IntroductionHaematospermia is an uncommon clinical condition that may be associated with prostate cancer. The optimal investigation of haematospermia is unknown. The aim of this study was to investigate haematospermia as a presenting symptom of significant pathology and to assess the diagnostic value of magnetic resonance imaging (MRI).Material and methodsPatient and treatment parameters were collected from a practice cohort of men referred to a urology center presenting with haematospermia. We used a multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Turo et al (2018) reported the outcomes of 125 consecutive patients, of whom 107 were evaluated with mpMRI. After adjusting for PSA, DRE and age, they found that mpMRI was a significant predictor of PCa diagnosis.…”
mentioning
confidence: 99%
“…Turo et al (2018) reported the outcomes of 125 consecutive patients, of whom 107 were evaluated with mpMRI. After adjusting for PSA, DRE and age, they found that mpMRI was a significant predictor of PCa diagnosis.…”
mentioning
confidence: 99%